Mechanical Loading and Bone - Jonathan H. Tobias (Frontiers Research Topics, 2016)
This research topic is focused on recent advances in our understanding of effects of mechanical loading on the skeleton, and research methods used in addressing these. Though it is well established that mechanical loading provides an essential stimulus for skeletal growth and maintenance, there have been major advances recently in terms of our understanding of the molecular pathways involved, which are thought to provide novel drug targets for treating osteoporosis. The articles included in this topic encompass the full spectrum of laboratory and clinical research, and range from review articles, editorials, hypothesis papers and original research articles. Together, they demonstrate how mechanical loading underpins many aspects of bone biology, including the pathogenesis and treatment of osteoporosis and other clinical disorders associated with skeletal fragility.